Determinants of the use of mortgage credit by Bogota homes (2018)
Mortgage credit is recognized in Colombia as one of the most used tools to obtain homeownership. This research identifies the main determinants of mortgage credit and estimates the influence of factors such as education, income and employment in the probability of making effective use of such credit by households in Bogota. In order to aim that purpose, this paper makes a description of regulatory framework for access to housing and the financial conditions established by major banks. Subsequently, and bases on the data gathered by the multipurpose survey made in 2014 for Bogota, a Logit model was estimated to establish the probability of use of credit for the purchase of housing. The results suggest that age, income and job stability influence the decision to use mortgage credit, however, the most important factor is given by the level of education.